Cranioplasty following decompressive craniectomy in traumatic brain injury: Experience at Level - I apex trauma centre - Basheer, Noufal; Gupta, Deepak; Mahapatra, AK; Gurjar, Hitesh (Indian Journal of Neurotrauma, 2010)
Complications after cranioplasty following decompressive craniectomy are often underreported. A review of the complications helps to suggest measures to improve the care of these patients. We provide a review of all complications of cranioplasty with autologous or synthetic materials in this article. All patients who had undergone cranioplasty following decompressive craniectomy at JPN Apex trauma centre, AIIMS from Jan 2008 till 2010 April were included in the study. Demographic data, indications for craniectomy, materials used, methods of autologous bone storage and all perioperative complications were recorded. Total 114 patients were studied. Mean duration between decompressive craniectomy and cranioplasty was 207.6 ± 28.2 days (Mean ± SD) with a range of 50 to 840 days. The overall postoperative complication rate was 23% (26/114) of which 16 patients (14 %) had to undergo reoperation after cranioplasty. Bone flap infection was the commonest accounting for 10 (62.5 %) of the reoperations. Even though considered as simple procedure, cranioplasty is associated with significant complications requiring reoperation. There was no correlation of complications or need for reoperation with type of materials, storage of the bone or timing of surgery. A seemingly smaller neurosurgical operation requires good surgical approach to minimize morbidity associated with cranioplasty.
Keywords: Cranioplasty; decompressive craniectomy; severe head injury